Reflection Loss Improvement by Cerium Addition in Chitosan-Hydroxyapatite Film as Stealth Drone Candidate - Riyanti Putri; Agus Eko Prasojo; Ardyan Lazuardy; Reza Anitasari; Fidela Aurellia Salsabila; Nugroho Adi Sasongko; Yusuf Bramastya Apriliyanto; Anggi Khairina Hanum Hasibuan; Dea Dwi Ananda (Indonesian Journal of Chemical Studies, 2025)
Radar is a detection and tracking technology commonly applied to monitor environmental conditions. Its ever-growing capabilities pose a serious challenge to military operations because they increase the risk of being detected by the enemy. On the other hand, unmanned aircraft (drones) are increasingly widespread in gathering information. However, the effectiveness of this technology can be reduced due to exposure to radar waves that allow detection. Therefore, developing coating materials that can absorb radar waves is an urgent need to increase the effectiveness of military equipment. The composites developed were derived from chitosan obtained from crustacean waste, hydroxyapatite from eggshell waste, and the rare earth metal cerium obtained from Lapindo Mud. Composites containing cerium metal (Ce) have higher radar signal absorption capabilities than samples without Ce, as evidenced by VNA measurements showing increased absorbance in the 100 MHz - 8.5 GHz frequency range. SEM tests indicate that cerium particles increase the density and homogeneity of the pore structure, with a size range of 17–24 µm. FTIR characterization revealed that Ce was physically bound to the chitosan-HAp composite. Mechanically, the composite with Ce had a maximum tensile stress of 9.512 MPa and a strain of 9.512%, while without the addition of Ce, a stress of 9.529 MPa and a strain of 25.512% was obtained. These findings indicate that integrating rare earth metals in chitosan-HAp composites can improve the material's capability to absorb radar waves, thus having broad prospects for applications in defence technology.